Evaluation of apical transportation by three rotary systems in extracted teeth with curved canals = Evaluación de la transportación apical con tres sistemas rotatorios en dientes extraídos con conductos curvos - Ortiz Rocha, Ana Laura; Dávila Pérez, Claudia; Vitales Noyola, Marlen; Méndez González, Verónica; González Amaro, Ana María (2020)
The aim of this study was to compare the apical transportation in extracted teeth using three different rotary nickel-titanium systems (Mtwo, Hyflex CM, and Typhoon). Sixty extracted first molars were randomly divided into three groups (n=20 in each group) with similar root canal curvatures (25-52 degrees). All root canals were prepared to size 30 using a crown-down preparation technique for each rotary system. Loss of working length and apical transportation were determined by X-ray evaluation. Comparisons between the groups were performed using one-way analysis of variance (ANOVA) or Kruskal-Wallis tests, and the post hoc analyses employed were Dunn's or Tukey's multiple comparison tests. No significant differences were detected between the different rotary systems in the loss of working length and apical transportation. This in vitro study showed that the use of these three rotary systems are safe and useful for instrumentation in curved canals; however, further in vivo research is essential to compare the effectiveness and safety of these systems for use in curved canals.
El objetivo del presente estudio fue comparar la transportación apical en dientes extraídos utilizando tres sistemas rotatorios de níquel-titanio (Mtwo, Hyflex CM y Typhoon). Sesenta primeros molares extraídos se dividieron aleatoriamente en tres grupos (n=20 en cada grupo) con curvaturas del conducto radicular similares (25-52 grados). Todos los conductos radiculares se prepararon usando una técnica corono apical para cada sistema rotatorio. La pérdida de la longitud de trabajo y la transportación apical se determinaron mediante evaluación radiográfica. Las comparaciones entre los grupos se realizaron utilizando análisis de varianza de una vía (ANOVA) o Kruskal-Wallis, y los análisis post hoc empleados fueron las pruebas de comparación múltiple de Dunn o Tukey. No se detectaron diferencias significativas entre los diferentes sistemas rotatorios en la pérdida de la longitud de trabajo y transportación apical. Este estudio demostró que el uso de estos tres sistemas es seguro y útil para su instrumentación en conductos curvos; sin embargo, investigación in vivo es necesaria para comparar la efectividad y seguridad de estos sistemas para su uso en conductos curvos.
En revista Odóvtos, vol. 22, no. 3 (septiembre-diciembre 2020)
Descripción basada en el contenido visto el 10 de octubre, 2024
También disponible en formato HTML y EPUB